Eksplorasi Konsep Allah yang Berkuasa dalam Penderitaan Manusia: Perspektif Regalitas Yesus dalam Yoh. 18:28–19:16a - Kusuma, Elicia; Letsoin, Yetva Softiming; Merong, Paulus Febrinam (Perspektif, 2025)
This paper aims to explore the kingship of Jesus within the context of human suffering, focusing on how the power of God remains present even amid situations of apparent powerlessness. Employing an analytical approach to the Gospel of John, this study examines the dialogue between Jesus and Pilate as well as the symbolism of the crown of thorns, which both highlight the nature of His regal identity. The methodology combines textual and theological analysis, emphasizing the Christological dimension that links Jesus’ suffering to God's salvific plan. The findings reveal that Jesus’ authority as King is not expressed through domination but is manifested through sacrifice and humility. In His experience of suffering, God demonstrates that He does not remain passive but actively engages in the redemption of human affliction. This paper concludes that the self-offering of Jesus redefines the meaning of suffering and invites readers to recognize God's presence in the midst of life’s trials.